Domestic travel behaviour among Generation Y / Farhan Faat, Nurul Hazirah Mohd Nasir and Nik Mohd Shahril Nik Mohd Nor - Faat, Farhan; Mohd Nasir, Nurul Hazirah; Nik Mohd Nor, Nik Mohd Shahril (faculty of Hotem Mangement and Tourism, Universiti Teknologi MARA, Puncak Alam Campus, 2017)
Youth travelers normally have a limited budget in exploring new destinations. Despite having a high curiosity and relaxation time, it has been found that youth travelers have high assumptions with respect to the significance of quality for cash they spend for travelling. The purpose of this study is to delve about the travel behavior and travel purpose among the youth travelers in Malaysia. A total of 210 respondents, which has been arbitrarily chosen in the Eastern states of Malaysia were included in the study. The surveys were analyzed to measure the variables of the study comprised of travel behavior and travel purpose. The results of the study likewise described that the youth travel behavior varied depending on the travel purposes. As a result, this study provides information for tourism marketers in producing suitable promotional tools to attract youth travelers.